Fabrication of polyvinylidene fluoride (PVDF) ultrafiltration hollow fiber membranes by modified thermally induced phase separation - Chen, Ningyuan (Nanyang Technological University, 2024)
Due to its exceptional physical and chemical properties, polyvinylidene fluoride (PVDF) membranes fabricated by thermally induced phase separation (TIPS) find extensive applications in various membrane-based separation processes. However, TIPS membranes are frequently categorized as microfiltration membranes due to their larger pore size (> 100 nm), limiting their application scope. This thesis presents the development of innovative methods to produce TIPS ultrafiltration membranes (pore size < 100 nm) with superior filtration performance and mechanical properties, which significantly broaden their industrial applications. Amphiphilic pore formers polyethylene glycol 400 (PEG400) and hydrophilic non-solvents triethylene glycol (TEG) were first introduced into the TIPS method. The synergistic effect of the PEG400 and TEG improved the permeability of the membranes dramatically. Furthermore, the addition of NaCl in the coagulation bath can be used to control the migration of PEG400 in polymer dope, which further improves the permeability and fine-tune the pore size of the fabricated membranes. This thesis expands the range of additives used in the TIPS process and demonstrates the pore-forming mechanism of TIPS PVDF membranes fabricated with pore formers.